Experimental investigation on flow condensation of methane in a horizontal smooth tube. (June 2017) - Zhuang, X.R.; Chen, G.F.; Zou, X.; Song, Q.L.; Gong, M.Q.
Highlights: Flow patterns of adiabatic and condensation conditions of methane were presented. Condensation heat transfer and pressure drop of methane were studied experimentally. The impact of fluid-to-wall temperature difference in a wide range was studied. An improved heat transfer correlation for different flow patterns was carried out. Abstract: An experimental investigation on flow visualization of adiabatic and condensation conditions as well as condensation heat transfer coefficient and pressure drop of methane in a horizontal smooth tube was carried out. The tests were conducted at saturation pressure of 2–3.5 MPa with mass flux of 99–255 kg m −2 s −1 and fluid-to-wall temperature difference of 4.8–20.2 K throughout the vapor quality range. The effects of mass flux, saturation pressure, vapor quality and temperature difference were studied and discussed. In order to expand the range of temperature difference, some condensation heat transfer coefficients of ethane with larger temperature differences (19.7–39.2 K) were also reported in this paper. The experimental data were compared with many well-known correlations of condensation heat transfer coefficient and pressure drop. An improved heat transfer correlation for different flow patterns was proposed and predicted the experimental results well with a mean absolute relative deviation of 6.86%.